Bacterial endocarditis, mitral regurgitation, and intra-atrial thrombosis following mitral valve replacement. Issue 1 (January 1968) - Windsor, Harry M.; Fagan, Paul; Shanahan, Mark X.
Abstract : Bacterial endocarditis with positive blood culture occurred on six occasions in a series of 140 mitral valve replacements. In three of these, extensive detachment of the prosthesis with severe mitral incompetence resulted. Re-operation was undertaken in two of these cases. Intra-atrial thrombosis occurred twice. In three other cases, in which intra-atrial thrombosis occurred, infection was strongly suspected to have been the responsible factor. Mitral regurgitation presented no difficulty in diagnosis, as all patients had severe congestive cardiac failure and typical physical signs. Confirmation was established by cinéangiography. Intra-atrial thrombosis presented difficulty in diagnosis. A persistently positive blood culture, continued pyrexia, and a history of sepsis were the most consistent and significant findings in the cases reported. The antibiotic regime described by Amoury and his colleagues has been used for the past year. There has not been a single case of bacterial endocarditis, intra-atrial thrombosis, or wound infection in 120 consecutive valve replacements on this regime. Because of the high mortality associated with intra-atrial thrombosis, and the close association between endocarditis and thrombosis, the presence of endocarditis with or without regurgitation might well be a compelling reason for re-operation. The mortality from these complications could, we believe, be reduced by the use of a more extensive antibiotic cover and a more vigorous attitude to surgical intervention. We have not had to consider re-operation since adopting the policy outlined, as these complications have not occurred.